Drift to Authoritarianism: The Changing Managerial Styles of the U.S. Executive Overseas - Alpander, Guvenc G. (Journal of International Business Studies, 1973)
This study places emphasis upon the interaction of the internal and external environment of the firm with the use, choice, personalities and contributions of executives operating in different environments and settings. The author concludes that the change in managerial style results in a shift in emphasis from employee orientation to task orientation, and from a participative approach to a more authoritarian approach.